Pengaruh Pendidikan Kesehatan Terhadap Pengetahuan Ibu Hamil Tentang Pencegahan Penularan HIV dari Ibu ke Anak (PPIA) - Triana, Hani; Purnasari, Henni (Jurnal Kesehatan, 2023)
More than 90% of direct transmission cases of HIV infection in children and infants occur vertically from the mother during pregnancy. One of the efforts to prevent transmission from mother to child is through the Program of Transmission Prevention of HIV from Mother-to-Child (PMTCT). PMTCT services are integrated into the Maternal and Child Health (MCH) package at all levels of healthcare. Health education is one of the methods applied in combating HIV-AIDS. Health education helps modify behavior and enhance knowledge about HIV-AIDS, thereby preventing transmission, especially from mother to child. The objective of this study is to improve mothers’ knowledge regarding the prevention of HIV transmission from mother to child (PMTCT). This research is a quantitative study with a pre-experimental design using a one-group pretest-posttest design. The population and sample for this study consisted of 84 pregnant women receiving antenatal care (ANC), selected using accidental sampling. The data collection instrument used in this study included health education materials presented through PowerPoint, reflection, and a questionnaire. Analysis results indicate that the respondents’ knowledge level increased after receiving health education (posttest) compared to before (pretest). Based on the Wilcoxon Matched Pairs Test, the Z-score was -7.318 with a significant level (α) of 0.000 (2-tailed) (or p-value=0.000 <0.05), thus accepting the alternative hypothesis (H1). In conclusion, this study demonstrates a significant difference in pregnant mothers’ knowledge about PMTCT before and after receiving health education.